Active-Modified Atmosphere Packaging of Ready-to-Eat Pomegranate (Punica granatum L.) Arils at Ambient Temperature for Extending Shelf-Life - Preethi Rokalla; Baskaran Stephen Inbaraj; Praveen Kumar Dikkala; Kandi Sridhar; Daniel Smith Dasi; Lalitha Koka; Ramalakshmi Munakala; Ranjith Galipothula; Kavitha Swarupa Rani Chelli; Naveen Kumar Kalletlapally (Agriculture, 2022)
Modified atmosphere packaging (MAP) has been widely applied to extend the shelf-life of fresh-cut produces, such as ready-to-eat pomegranate arils. However, many studies used MAP to extend the shelf-life of arils at 3, 4, and 15 °C. The evidence suggested that MAP can extend the shelf-life of arils at an ambient temperature. Therefore, we attempted to extend the shelf-life of ready-to-eat pomegranate arils using active MAP at an ambient temperature and evaluated its chemical, quality, and microbial properties. Samples were flushed with specific gas compositions of oxygen (O2) and carbon dioxide (CO2) at an ambient temperature and 60 ± 2% relative humidity (RH). The findings demonstrated that active MAP increased the titratable acidity (0.32–3.64%), anthocyanins (0.27–0.42 g/L), reducing sugars (1.06–10.13%), and total soluble solids (15–19 °Brix), while it decreased the pH (3.20–3.54) and hardness (4.60–9.40 N) with a microbial load of ≤5 log CFU/g at ambient temperature for 5 days. Ultimately, active MAP could be an effective technique to be used in ready-to-eat produce industries and has the potential to guarantee a longer shelf-life at ambient temperature without the use of refrigerator facilities.